Ego dan Emosi Tokoh Ayah dan Anak dalam Novel Seribu Wajah Ayah Karya Nurun Ala: Tinjauan Psikologi Sastra - Dilma, Thesya Ramadhani (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2025)
This study examines the ego and emotions of the father and child characters in the novel